Revenue from UNI's Technological Services from 2009 to 2023 - Salazar Quiroz, Gerald (2024)
This case study presents the behavior of the resources directly collected for technological services, defined as the sum of the RdR for research and development services (1.3.39.23) and third-party services (1.3.39.29), at the National University of Engineering during the period 2009 to 2023. Under a technological extensionism approach, the revenues collected and their management by the UNI can be considered as indicators of how the university is fulfilling its role as a provider of knowledge in the economy. The data obtained show a downward trend, especially in third-party services, while R&D services remain stable on average over the years but have not yet recovered pre-COVID-19 revenue levels. This work also proposes modernization lines for the university's technological services management, based on PCM provisions regarding commercial activities and determining costs for services exclusively provided by public institutions.